Growing up with a pacemaker. (25th November 2020) - Poels, P; Vermeulen, J; Gewillig, M; Meyns, B; Willems, R
Abstract: : Indications for pacemakers in young children are rare. In our university hospitals, on average 8 patients/year received a pacemaker in this age group between 2001 and 2015 for a drainage area of 4 million people. In 28% this is for congenital heart block and in 69% for bradycardia after surgical repair of congenital structural heart disease. Despite the extensive range of patient information about pacemakers, we felt a need for targeted material for young patients, who have an indication for a pacemaker, and their family. We wanted to provide this information to this specific group in a creative, accessible and clear way, taking into account their way of thinking. In addition, we also wanted to involve the near and wider environment of the child (family, school, sports club, etc.), and to provide them with tools to better deal with the medical situation. For the little children we created a stop-motion story in which sinus node disease (SND) and AV block (AVB) are represented by a character: Bob Sparkle (Bob Prikkel in Dutch for SND) and Boris Sparkle (Boris Prikkel for AVB). Bob and Boris get into trouble and are rescued by Pacemaker, the third character in the films. This story is preceded by an informative part for parents and older children in which the normal functioning and conduction system of the heart is explained. Based on the films, we designed customized information brochures for +12 and −12 year-old children. The brochure for +12 includes the same information as the adult version, but in more comprehensible language. The figures Bob and Boris were added throughout this brochure as a sort of common thread. For the −12 group we designed 2 reading books in which the story of Bob / Boris is told. The −12 booklets can be included in a cover along with the +12 brochure, so that the parents can estimate for themselves what is most suitable for their child. We conducted a survey on how this information was received by patients and their relatives.61 families were contacted by e-mail to fill in a questionnaire using a 5-point Likert Scale. The survey assessed the following three items: graphic design, intelligibility and aid in coping with illness. Currently we have received answers from 12 patients or their relatives. Overall, there was a positive reception of the different informative tools (agree or strongly agree: booklets: 92.6%; brochure: 77.2%; films: 81.3%). Funding Acknowledgement: Type of funding source: None